Differences in hypertension phenotypes between Africans and Europeans: role of environment. Issue 7 (July 2020) - Faconti, Luca; McNally, Ryan J.; Farukh, Bushra; Adeyemi, Olusoji; Cruickshank, J. Kennedy; Wilkinson, Ian B.; Chowienczyk, Phil J.; Ojji, Dike
Abstract : Objectives: Hypertension phenotypes differ between Africans and Europeans, with a greater prevalence of low renin salt-sensitive hypertension and greater predisposition to adverse cardiac remodelling in Africans. To elucidate the roles of inheritance and environment in determining hypertension phenotypes in sub-Saharan Africans and white-Europeans, we compared phenotypes in white individuals in the UK ( n  = 132) and in African individuals in the UK ( n  = 158) and Nigeria ( n  = 179). Methods: Biochemistry, blood pressure, left ventricular structure (echocardiography) and 24-h urinary collections of sodium and potassium were measured. Results: Twenty-four-hour urinary sodium/potassium ratio was lower in individuals living in Europe (both African and white: 2.32 ± 0.15 and 2.28 ± 0.17) than in individuals in Nigeria (4.09 ± 0.26, both P  < 0.001) reflecting proportionately higher potassium intake in Europeans (African or white) than African residents. Plasma renin was lower in Africans irrespective of residency than white Europeans, but aldosterone was higher in Africans in Europe than those in Africa (466.15 ± 32.95 vs. 258.60 ± 17.42 pmol/l, P  < 0.001). Left ventricular mass index adjusted for blood pressure and other confounders was greatest in Africans in Europe (103.27 ± 2.32 g/m 2 ) compared with those in Africa (89.28 ± 1.98 g/m 2 ) or white Europeans (86.77 ± 2.63 g/m 2, both P  < 0.001). Conclusion: Despite a similar low renin state in African origin individuals living in Europe and Africa, a higher aldosterone level, possibly related to higher potassium intake or other environmental factors, may contribute to greater cardiac remodelling in Africans in Europe. Abstract : Supplemental Digital Content is available in the text